Peluang dan Tantangan Pengintegrasian Learning Management System (LMS) dalam Pembelajaran Matematika di Indonesia - Ibnu Rafi; Fina Fitri Nurjannah; Iqlima Ramadhani Fabella; Sri Andayani (Jurnal Tadris Matematika, 2020)
This literature review aimed to describe the opportunities and challenges of integrating the Learning Management System (LMS) in mathematics learning, especially in terms of the non-technical aspects. Because many LMS platforms which can be integrated into learning process, this review only discusses the three LMS platforms which are common, namely Moodle, Edmodo, and Schoology. This review was conducted with the method as proposed by Templier and Paré (2015), in which the literature materials consisted of journal articles, proceedings, and official websites of LMS. The results of this review showed that integrating the LMS in mathematics learning indicated opportunities in terms of the positive impact which can be obtained from integrating the LMS. On the other hand, the identified challenges were about how mathematics content or materials were organized through integrating the LMS, providing feedback, and maximizing the online discussion facility provided by LMS. Therefore, to obtain the positive impact from integrating the LMS into mathematics learning, teachers should pay attention to these three challenges.